Solve the system using 2 methods. x+2y=6 2x+6y=8
- print Print
- list Cite
Expert Answers
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
x+2y=6...(1)
2x+6y=8.....(2)
First let us multiply (1) with -2 and add to (2)
-2x-4y=-12
2x+6y=8
==> 2y=-4
==> y=-2
==> x= 6-2y = 6-2(-2)= 6+4=10
Related Questions
- Solve the system: x+2y -z=3 2x-y+2z=8 x+y+z=3
- 1 Educator Answer
- solve the equation: 2^(2x-1)= 8^x
- 1 Educator Answer
- 2x-3y = 8 x+2y=3 solve x and y
- 1 Educator Answer
- Solve the system x+2y=3 4x+5y=6
- 1 Educator Answer
- Solve the system: x+2y = 5 2x-3y = 2
- 2 Educator Answers
To solve x+2y=6...(1) andÂ 2x+6y=8, using two methods:
Solution:
Substitution method:
From (2) we get: 2x = 8-6y Or x = (8-6y)/2 =4-3y. We substitute x = 4-3y in the equation (1):
4-3y+2y = 6. Or 4-y = 6. Or 4-6 = y. Or y = -2.
Substituting y= -2 in (1), we get: x+2(-2) = 6. Or x= 6+4 = 10.
Elemination method:
2y appears in eq (1) and 6y in eq (2). So 3*eq (1)- eq(2) eliminates y:
3*Eq(1) - eq(2): 3(x+2y)-(2x+6y) = 3*6-8 =10.Or
3x-2x = 10. Or x = 10.
Using x = 10, in (2), we get: 10*2 - 6y = 8. Or 6y = 8-20. Or 6y = -12. Or y = -12/6 = -2.
The first method is the substitution method.
We'll write one variable depending on the other one.
From the first equation, we'll choose to write x=6-2y
Now we'll substitute x from the second equation, by it's expression and we'll get an expression in y.
2(6-2y)+6y=8
12-4y+6y=8
12+2y=8
We'll subtract 12 both sides:
2y=8-12
2y=-4
y=-2
Now, we'll substitute y in the x expression.
x=6-2y
x=6+4
x=10
The second method is to reduce one variable from the both equations of the system.
We'll reduce x and for this reason, we'll multiply the first equation by -2 and we'll get.
-2x-4y=-12
Now we'll add the new equation to the second one.
-2x-4y+2x+6y=-12+8
2y=-4
y=-2
x=10
Student Answers